Sex Ratio and Body Mass of Adult Herbivorous Beetles Depend on Time of Occurrence and Light Conditions. - Adrian Łukowski; Ewa Mąderek; Marian J Giertych; Piotr Karolewski (PLoS ONE)
Body mass and sex ratio (F/M) of folivorous insects are easily measured parameters that are commonly used to assess the effect of food quality, living conditions, and preferences on the selection of favourable sites for offspring. A study was conducted on the polyphagous beetle, Gonioctenaquinquepunctata (a pest of the native Prunus padus and alien P. serotina) and on the monophagous beetle, Alticabrevicollis coryletorum (a pest of Corylus avellana). Both species have a similar life cycle with emergence of current-year adults in summer, and reproduction of 1-year-old insects in spring. A. brevicollis coryletorum feeds primarily on sunlit shrubs, while G. quinquepunctata prefers shaded leaves. The present study assessed the effect of time of occurrence(insect age) on body mass in both sexes and on the sex ratio F/M, taking into account the influence of light conditions associated with their favoured food source (sunlit vs. shaded leaves). We hypothesized that a change in body mass in current-year insects would be determined by the amount of consumed food, while the sex ratio would be stable, when in 1-year-old insects females would die shortly after oviposition, while males would be active for a prolonged time. Results confirmed the hypothesis that changes in mass of current-year beetles was determined by the amount of food intake. We also found that in spring, unfertilized females coexist with fertilized ones and that the latter females live for some time after oviposition; resulting in fluctuations of the mean mass for females. In both species, 1-year-old beetles were heavier than current-year. The preference of A. brevicollis coryletorum for sunlit leaves results in a higher body weight than in G. quinquepunctata in both seasons. The data are consistent and indicate seasonal fluctuations in body mass and changes in the sex ratio in 1-year-old beetles, due to the entrance into their reproductive period.